ENABLING TEAM INNOVATION BY OPTIMIZING RESOURCE AVAILABILITY AND PROMOTIVE VOICE BEHAVIOR - Rahma Frida Ratri; Ahmad Rizki Sridadi (Jurnal Bisnis Manajemen, 2022)
Team innovation has become a decisive aspect of achieving organizational success since today’s environment relies on collaborative aspects. Thus, the purpose of this study is to examine some critical factors which influence perceived team innovation, such as resource availability, promotive voice behavior, willingness to discuss and perceived team knowledge utilization. The data were collected from 100 employees as team members in a company engaged in the automotive support industry. The results of this study using PLS (Partial Least Square) proved that: (1) there is a significant relationship between resource availability and perceived team innovation, (2) resource availability has a significant effect on promotive voice behavior, (3) promotive voice behavior is a significant predictor of perceived team innovation, (4) promotive voice behavior has a significant impact on willingness to discuss, (5) willingness to discuss has a significant relationship with perceived team innovation, (6) promotive voice behavior has a significant effect on perceived team knowledge utilization, (7) perceived team knowledge utilization has a significant effect on perceived team innovation. These findings highlight the importance of the factors mentioned earlier to enhance perceived team innovation in the organization.